EMLEK YÖRESİ VE EMLEK AĞZI UZUN HAVALARININ ANALİZİ - ÖZKAN MORAN; NACİ MADANOĞLU; SONER ALGI; ALİ KEREM APAYDIN (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2024)
Emlek region, which covers some districts and villages of Sivas, Yozgat, Kayseri and Tokat provinces, hosts a very rich culture in terms of minstrel tradition. Music, which is considered as an important element of this culture, has spread all over the country today on the saz of the minstrels of Emlek region. Although Emlek accent unmetered folk songs, which are in the unmetered folk song genre in terms of usul, have an important place in Turkish folk music literature and music education, the lack of academic studies on this subject has been remarkable. In this study, it is aimed to contribute to the literature on the Emlek region by examining the history, cultural texture of the Emlek region, the minstrel tradition in the region and the literary and musical identity of the 14 unmetered folk songs identified within the scope of the study. For this purpose, the relevant literature, archives and compilations were scanned, and detailed analyses on the region and the unmetered folk songs of the region were tried to be made by notating the sound recordings whose notes could not be reached. When the analysed works were examined from a literary point of view, it was determined that the subjects of love, infatuation, longing, separation, natural disasters, reproach to the disaster were dealt with, the majority of the poems were kosma written in 11 syllable meter and one of them was semai written in 8 syllable meter, they contained added words, but added words independent from the poem were not used frequently. In the musical analyses, it was concluded that the works decide on the note la, the notes B flat 1, B flat 2 and F sharp 3 are used as modifying signs, generally exhibit a descending-descending course, and have a sound width between 5 and 17 voices.